Manajemen Privasi Generasi Z Menghadapi Komersialisasi Data Pribadi di Media Sosial - Pratama Wasisto Aji; Prahastiwi Utari; Sudarmo (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
Generation Z now uses social media as a place and a source of social capital. There are a lot of issues that come along with social media usage growing. One of them is social media corporations' marketing of user data. This study aims to examine how Generation Z manages privacy in light of the issue of personal data monetization. This research approach employs descriptive quantitative, and the convenience sampling method is used for sampling. In Central Java and the Special Region of Yogyakarta, 100 Generation Z respondents with ages ranging from 1995 to 2010 participated in the study. This study analyzes the privacy policies of the Meta corporation, which is in charge of two social media platforms, especially Facebook and Instagram, to contextualize the several ways that personal data is used for commercial purposes. This study combines objective and subjective privacy management using an integrative privacy management theory. According to the study's findings, users of social media carefully read the terms of service before using them and are aware of what is done with their personal information. Users' concerns about the dissemination of their private information on social media are impacted by this.